Conceptual framework of Tenaga Nasional Berhad (TNB) cost of service (COS) model - Zainudin W.N.R.A.; Ishak W.W.M.; Sulaiman N.A. (Institute of Physics Publishing, 2024)
One of Malaysia Electricity Supply Industry (MESI) objectives is to ensure Tenaga Nasional Berhad (TNB) economic viability based on a fair economic electricity pricing. In meeting such objective, a framework that investigates the effect of cost of service (COS) on revenue is in great need. This paper attempts to present a conceptual framework that illustrate the distribution of the COS among TNB's various cost centres which are subsequently redistributed in varying quantities among all of its customer categories. A deep understanding on the concepts will ensure optimal allocation of COS elements between different sub activities of energy production processes can be achieved. However, this optimal allocation needs to be achieved with respect to the imposed TNB revenue constraint. Therefore, the methodology used for this conceptual approach is being modelled into four steps. Firstly, TNB revenue requirement is being examined to ensure the conceptual framework addressed the requirement properly. Secondly, the revenue requirement is unbundled between three major cost centres or business units consist of generation, transmission and distribution and the cost is classified based on demand, energy and customers related charges. Finally, the classified costs are being allocated to different customer categories i.e. Household, Commercial, and Industrial. In summary, this paper proposed a conceptual framework on the cost of specific services that TNB currently charging its customers and served as potential input into the process of developing revised electricity tariff rates. On that purpose, the finding of this COS study finds cost to serve customer varies with the voltage level that customer connected to, the timing and the magnitude of customer demand on the system. This COS conceptual framework could potentially be integrated into a particular tariff structure and serve as a useful tool for TNB. Published under licence by IOP Publishing Ltd.